Facile Synthesis of Methanofullerenes in an Aqueous Two-Phase System under Photoirradiation Conditions - Iwai, Toshiyuki; Matsumoto, Fukashi; Hida, Koichi; Moriwaki, Kazuyuki; Takao, Yuko; Ito, Takatoshi; Mizuno, Takumi; Ohno, Toshinobu (Synlett, 2015)
Methanofullerenes, such as [6,6]-phenyl-C61-butyric acid methyl ester {[6,6]PC61BM (1a)}, were synthesized in good yields from the corresponding tosylhydrazones in an aqueous two-phase (o-dichlorobenzene–H2O) system under photoirradiation conditions. This simple and convenient procedure was adopted for the synthesis of thienyl analogues of PC61BM and its C70 analogue, PC71BM.
Keywords: photovoltaics; fullerenes; hydrazones; methanofullerenes; PCBM